Treatment of residual sodium and sodium potassium from fast reactors : review of resent accomplishments, challenges and technologies. (IAEA-TECDOC, 2015)
"This publication discusses a variety of treatment methods to be considered when dismantling components that still contain residual quantities of sodium or sodium potassium, several of which were presented as contributed papers to the IAEA session during the 5th International Conference and Exhibition on Decommissioning Challenges, in Avignon, France, 7-11 April 2013. The publication provides a synthesis of information presented during the session, which was developed further at a consultants meeting held in Vienna, 2-6 December 2013. Decommissioning challenges faced at eight different facilities in five different countries are discussed, as well as the achievements and lessons learned that are of value to the worldwide decommissioning community. The special session at the Avignon Conference on the treatment of residual sodium and sodium potassium was organized by the IAEA International Decommissioning Network, whose members also contributed to the drafting and review of this report. The IAEA officer responsible for this publication was P.J. O'Sullivan of the Division of Nuclear Fuel Cycle and Waste Technology."--Foreword